Efficacy of rituximab therapy in children with nephrotic syndrome: a 10-year experience from an Iranian pediatric hospital - Behnaz Bazargani; Zahra Noparast; Leila Khedmat; Daryoosh Fahimi; Seyed Taher Esfahani; Mastaneh Moghtaderi; Arash Abbasi; Azadeh Afshin; Sayed Yousef Mojtahedi (BMC, 2022)
Abstract Background There are controversy results in the optimal management of children with steroid-dependent and steroid-resistant nephrotic syndrome (SDNS, SRNS). This study aimed to determine the efficacy and safety of rituximab (RTX) in these pediatric patients. Methods Medical records of 1-18-year-old Iranian children with SDNS (n = 26) and SRNS (n = 22) with a follow-up for at least 24 months were included from 2009 to 2019. The short- and long-term responses to RTX were respectively evaluated to determine the random protein-to-creatinine ratio after 6 and 24 months and classified as complete (CR) and partial (PR) remission or no response. Results Male patients (n = 26) were slightly predominate. The median age of patients at the time of RTX therapy was 8.6 ± 4.01 years. At the end of the 6-month follow-up, CR and PR occurred in 23 (47.9%) and 12 (25%) patients, respectively. Of 23 patients with CR, 18 (69.2%) and 5(22.7%) had SDNS and SRNS, respectively (p < 0.005). However, only 18 (37.5%) of patients after 24 months had been in CR. No significant difference in the CR rate was found between the two groups. RTX was more effective when administered during the proteinuria-free period (p = 0.001). Conclusion In the short term, RTX significantly was efficient in inducing complete or PR in SDNS and SRNS patients. However, the favorable response rate in a long-term follow-up was insignificantly lower between the two groups.